2016
DOI: 10.1002/trtr.1523
|View full text |Cite
|
Sign up to set email alerts
|

Visual Thinking Strategies: Teachers' Reflections on Closely Reading Complex Visual Texts Within the Disciplines

Abstract: The authors offer a new perspective on close reading that uses a range of multimodal texts to capitalize on the visual nature of contemporary society and to support literacy within the academic disciplines. Specifically, a qualitative study explored teachers' perspectives on the use of Visual Thinking Strategies (VTS), a practice borrowed from museum educators that replicates close reading processes, to support literacy learning within subject areas. The analysis revealed teachers' beliefs that VTS supported s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
22
0
2
Order By: Relevance
“…My plan for the week did not include integrating media texts depicting campus protesters or racial tension, but these texts seeped into our classroom curriculum nonetheless as texts to respond to and critically inspect. We were in the middle of a unit about making inferences from pictures and studying the text before drawing conclusions using Visual Thinking Strategies (Cappello & Walker, 2016). I knew that all of my students would benefit from a discussion about the racial tension in our community.…”
Section: Being With: Mishamentioning
confidence: 99%
“…My plan for the week did not include integrating media texts depicting campus protesters or racial tension, but these texts seeped into our classroom curriculum nonetheless as texts to respond to and critically inspect. We were in the middle of a unit about making inferences from pictures and studying the text before drawing conclusions using Visual Thinking Strategies (Cappello & Walker, 2016). I knew that all of my students would benefit from a discussion about the racial tension in our community.…”
Section: Being With: Mishamentioning
confidence: 99%
“…All of these components affect the interpretation of the visual reader. Not surprisingly, many researchers (e.g., Cappello & Walker, ; Pantaleo, ; Serafini, ) have agreed that reading visual images is an important aspect of reading multimodal texts, including graphic novels. Clearly, a strategy for reading visual images, easily adaptable to the classroom, must occupy a central position in the suite of strategies we suggest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To teach visual literacy, we found a simple strategy used in art interpretation known as Visual Thinking Strategy (Cappello & Walker, ; Yenawine, ). The strategy consists of viewing a picture and walking students through three questions: What is happening in this picture?…”
Section: Developing Strategies To Teach Graphic Novelsmentioning
confidence: 99%
“…There has been much research about applying multimodal theories in school settings, especially through picture books (Callow, 2018a;Serafini, 2014;Sipe, 2008). Some studies have found that multimodal methods create safe environments for academic risk taking (Cappello & Walker, 2016;Franco & Unrath, 2014;Landorf, 2006). In addition, Franquiz and Brochin-Ceballos (2006) described how children's use of visuals created a safe space to "link cultural practices from home and community" (p. 7).…”
Section: Bringing Multimodal Perspectives To Belizementioning
confidence: 99%